2016
DOI: 10.1177/0193945916636629
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Beliefs About Caring for Patients With Traumatic Brain Injury

Abstract: Patients with traumatic brain injury (TBI) and their families rely on health care providers, particularly nurses, to provide accurate information, yet inaccurate beliefs about TBI have been found among nurses. Although prior studies have assessed nurses' beliefs about TBI recovery and rehabilitation, none have assessed specific beliefs about the nursing role to care for these patients. The purpose of this study was to investigate nurses' beliefs and learning preferences about caring for patients with moderate-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
38
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 55 publications
4
38
0
Order By: Relevance
“…More specifically, in another study, nurses caring for adult patients with moderate-to-severe TBI had similar inaccurate beliefs about treatment and sex-based patient differences after TBI (Oyesanya, Thomas, et al, 2016). The presence of inaccurate beliefs may suggest that nurses are providing inaccurate information to patients with TBI and their families (Ernst et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, in another study, nurses caring for adult patients with moderate-to-severe TBI had similar inaccurate beliefs about treatment and sex-based patient differences after TBI (Oyesanya, Thomas, et al, 2016). The presence of inaccurate beliefs may suggest that nurses are providing inaccurate information to patients with TBI and their families (Ernst et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Data were collected using the Perceptions of Brain Injury Survey (PBIS) (Oyesanya, Brown, et al, 2016; Oyesanya, Thomas, et al, 2016). This survey was created by adapting two surveys: 1) a survey about school speech-language pathologists’ perceived knowledge, perceived confidence, and beliefs to provide services to students with TBI (severity level unspecified) (Hux, Walker, & Sanger, 1996); and 2) a survey on nurses’ perceived knowledge regarding care of patients with mild TBI (Watts et al, 2011).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings showed that nurses had inaccurate beliefs about TBI relating to recovery and the nursing role, and had significant differences in learning preferences. These findings have implications for development of educational and training interventions specific to nurses to ensure that they have factual information about TBI and to clarify the nursing role [1].…”
mentioning
confidence: 97%
“…The purpose of this study was to investigate nurses' beliefs and learning preferences about caring for patients with moderate-to-severe TBI [1]. A cross-sectional survey was administered to 513 nurses at a Midwestern hospital between October and December 2014 (20.3% response rate).…”
mentioning
confidence: 99%